1994
DOI: 10.1037/0735-7028.25.4.466
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural competencies of doctoral interns at university counseling centers: An exploratory investigation.

Abstract: In this study the multicultural competencies of 141 doctoral interns at university counseling centers were explored. Results indicated that some educational variables were predictive of multicultural competencies. Interns who had received supervision for a multicultural counseling situation, attended more multicultural workshops, or taken more multicultural course work, reported greater multicultural knowledge and skills than did interns who had no such supervision, fewer workshop hours, or less course work. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 12 publications
3
56
1
Order By: Relevance
“…Findings from prior research (e.g., Bellini, 2002;Vinson & Neimeyer, 2003) and the current study have suggested that racial/ethnic minority counseling students and professionals tend to receive more multicultural counseling training and have a higher proportion of minority clients on their caseloads, which may, in turn, lead to higher perceived abilities to perform multicultural counseling Pope-Davis et al, 1994). In other words, the racial differences on multicultural counseling competency or self-efficacy may be due to how much multicultural counseling training and other relevant experience a counselor receives rather than being due to his or her race per se.…”
Section: Criterion Validity Of the Mcse-rd Scoresmentioning
confidence: 49%
See 1 more Smart Citation
“…Findings from prior research (e.g., Bellini, 2002;Vinson & Neimeyer, 2003) and the current study have suggested that racial/ethnic minority counseling students and professionals tend to receive more multicultural counseling training and have a higher proportion of minority clients on their caseloads, which may, in turn, lead to higher perceived abilities to perform multicultural counseling Pope-Davis et al, 1994). In other words, the racial differences on multicultural counseling competency or self-efficacy may be due to how much multicultural counseling training and other relevant experience a counselor receives rather than being due to his or her race per se.…”
Section: Criterion Validity Of the Mcse-rd Scoresmentioning
confidence: 49%
“…The literature on gender differences in multicultural counseling competence is not conclusive. Studying students in counseling and clinical psychology programs and doctoral interns at university counseling centers, Pope-Davis and his colleagues (PopeDavis, Reynolds, Dings, & Nielson, 1995;Pope-Davis, Reynolds, Dings, & Ottavi, 1994) found no gender differences on the MCI subscale and total scores or on the MCAS subscale scores. On the other hand, also using the MCI, Bellini (2002) found gender to be a significant predictor ( = .17) of multicultural counseling competency, with female vocational rehabilitation counselors reporting higher multicultural counseling competence than their male counterparts.…”
Section: Criterion Validity Of the Mcse-rd Scoresmentioning
confidence: 99%
“…The CCCS was developed to measure healthcare providers' perceptions of their critical cultural competence in a multicultural healthcare context. A number of frameworks and instruments have been developed to measure cultural competence, including the Cultural Self-Efficacy Scale [1,2], the Cultural Attitude Survey-Modified [3], the Cultural Awareness Survey [4], the Multicultural Sensitivity Scale [5], and the Multicultural Counseling Inventory (adopted scale) [6].…”
Section: Introductionmentioning
confidence: 99%
“…While the terms cultural competence, cross-cultural competence, inter-cultural competence, and multicultural competence have slightly different definitions, depending on the reference (Rasmussen & Sieck, 2015), we employ a definition which distills the common components from Pope- Davis, Reynolds, Dings and Ottavi (1994). This definition asserts that multicultural competence is "the ability to work and be effective with individuals who are of a different culture from yours [and includes an] appreciation of and sensitivity to the history, current needs, strengths, and resources of communities and individuals who historically have been underserved and underrepresented.…”
Section: Study Abroad and Multicultural Competencementioning
confidence: 99%